Mapping out the additive manufacturing landscape. Issue 3 (May 2015) - Bland, Stewart; Conner, Brett
<x xml:space="preserve">Abstract</x> There's no denying that additive manufacturing is receiving an enormous and increasing amount of interest from industry and academia alike. But how can companies navigate their way around this emerging landscape? Metal Powder Report spoke to Dr Brett Conner, lead author of new study in the journal Additive Manufacturing that introduces a system to map out potential products and help businesses make informed decisions.